High Levels of Physical Activity May Promote a Reduction in Bone Mineral Density in Peritoneal Dialysis - Raimundo, A. (2021)
Background and objectives: Peritoneal dialysis (PD) patients are expected to present lower levels of physical activity, unhealthy changes at the body composition level, and low levels of strength. Firstly, this study aimed to report the sex differences in physical activity, body composition and muscle strength and the relations among these variables. Secondly, we analyze the relationship between physical activity and biochemical parameters. Materials and Methods: Thirty-four patients (13 women and 21 men) participated in this study. Body composition was assessed by bioimpedance and dual-energy X-ray absorptiometry (DXA), and maximum isokinetic unilateral strength, analytical parameters and physical activity levels were evaluated. Results: The men showed higher values for weight, height, lean body mass, bone mineral content, bone mineral density (BMD) and total body water, while women showed higher values for the percentage of fat mass and hydration of lean body mass (p < 0.05). No differences between the sexes were found in different levels of physical activity; however, males registered significantly higher values for isokinetic strength variables except for knee extensor strength. BMD was positively related to sedentary activity and negatively related to moderate and vigorous activity (r = 0.383 and r = −0.404, respectively). Light physical activity was negatively correlated with albumin (r = −0.393) and total protein (r = −0.410) levels, while moderate/vigorous activity was positively correlated with urea distribution volume (r = 0.446) and creatinine clearance (r = 0.359) and negatively correlated with the triglyceride level (r = −0.455). Conclusions: PD patients with higher levels of physical activity present better results in terms of body composition and biochemical parameters. Additional studies should be conducted to clarify the relation between physical activity level and BMD.